Modeling and Simulation at the Interface of Nonclinical and Early Clinical Drug Development. (27th February 2013) - Visser, SAG; Manolis, E; Danhof, M; Kerbusch, T
Abstract : The role of modeling and simulation (M&S) in early drug development was discussed in a break out session of the European Medicines Agency/European Federation of Pharmaceutical Industries and Associations (EMA/EFPIA) M&S workshop held in December 2011 in London, UK. The discussions were focused on two themes: (i) M&S in nonclinical and early clinical drug development and (ii) M&S for first‐in‐human (FIH) dose selection. Illustrative case studies were presented and links are listed inTable 1 . Common objectives and next steps were identified, discussed, and agreed. CPT: Pharmacometrics & Systems Pharmacology (2013) 2, e30; doi:10.1038/psp.2013.3 ; advance online publication 27 February 2013